Fusaric acid induces hepatic global m6A RNA methylation and differential expression of m6A regulatory genes in vivo - a pilot study. Issue 6 (3rd June 2022) - Ghazi, Terisha; Nagiah, Savania; Chuturgoon, Anil A.
ABSTRACT: N6-methyladenosine (m6A) is an abundant epitranscriptomic mark that regulates gene expression to execute cellular developmental programmes and environmental adaptation. Fusaric acid (FA) is a mycotoxin that contaminates agricultural foods and exerts toxicity in humans and animals; however, its epitranscriptomic effects are unclear. We investigated the effect of FA on global m6A RNA methylation and mRNA expression levels of key m6A regulatory genes in C57BL/6 mouse livers. C57BL/6 mice ( n = 6/group) were orally administered 0.1 M phosphate-buffered saline (PBS) or 50 mg/kg FA. Mice were euthanized 24 h after oral administration, livers were harvested, and RNA was isolated. RNA samples were assayed for global m6A levels using an m6A RNA Methylation Quantification Kit. The mRNA expression of m6A regulators i.e. writers, erasers, and readers were measured by qRT-PCR. FA increased global m6A RNA methylation ( p < 0.0001) in mouse livers. FA increased the expression of METTL3 ( p = 0.0143) and METTL14 ( p = 0.0281), and decreased the expression of FTO ( p = 0.0036) and ALKBH5 ( p = 0.0035). The expression of YTHDF2 ( p = 0.0007), YTHDF3 ( p = 0.0061), and YTHDC2 ( p = 0.0258) were increased by FA in mouse livers. This study shows that the liver m6A epitranscriptome can be modified by FA exposure in an in vivo model and can be useful for identifying the molecular mechanisms whereby m6A RNA modifications influence the toxicological outcomes of FA exposure.